Temporary intravascular shunts and limb salvage in civilian vascular trauma - Martinelli, Ombretta; Miceli, Francesca; Cuozzo, Simone; Irace, Francesco Giosuè; Avenia, Stefano; Iannone, Immacolata; Clementi, Ilaria; Sapienza, Paolo; Bellini, Maria Irene (Frontiers in Surgery, 2023)
Background. Temporary intravascular shunts (TIVS) may allow a quick revascularization and distal reperfusion, reducing the ischemic time (IT) when an arterial injury occurs. Furthermore, TIVS temporarily restore peripheral perfusion during the treatment of concomitant life-threatening injuries, or when patients require evacuation to a higher level of care. Notwithstanding, disputes regarding TIVS use still remain, in view of the paucity of evidence in terms of potential benefits and with regards to the anticoagulation during the procedure. The aim of the present study was to assess TIVS impact, safety, and timing on limb salvage in complex civilian vascular traumas. in group A: 4.17 ± 2.37 vs 5.81 ± 1.26 hours. TIVS positively affected the probability of limb salvage (p=0.02). At multivariate analysis factors independently associated with limb salvage were: TIVS usage, the necessity of hyperbaric oxygen therapy and the total ischemic time. In group A there were 3 deaths and 1 major amputation; in group B, 2 deaths and 4 major amputations.Conclusions. TIVS use minimizes revascularization time and improves limb salvage probability. A multidisciplinary approach is recommended, and correct surgical timing is key to ensure the best outcome.